The Reconstructive Toolbox - Hallock, Geoffrey G. (Archives of Plastic Surgery, 2023)
Historically, the approach to any reconstructive challenge, whether intentionally or intuitively, can be seen to follow distinct guidelines that could aptly be called “reconstructive metaphors.” These have been intended to inform us as to the “what, “when” and “where” this attempt can best be achieved. Yet the “how” or means to accomplish this goal, usually also intuitively well understood, in a similar vein can now be expressed to be within our “reconstructive toolbox.” The latter will distinctly mirror our individuality and contain not only the various hardware that we deem essential, but also the means to access whatever technology we may be comfortable with. No toolbox, even if overflowing will ever be full, as potential options and the diversity they represent surely approaches infinity. But the truly excellent reconstructive surgeon will know when their toolbox is in any way lacking, and fears not remedying that deficiency even if the talents of another colleague must be sought, so as always to ensure that the patient will obtain the best appropriate treatment!
Keywords: reconstructive ladder; reconstructive elevator; reconstructive matrix; reconstructive toolbox